Mansonia uniformis (Diptera: Culicidae), a genus and species new to southwestern Asia, with a review of its medical and veterinary importance - Azari-Hamidian, Shahyad; Abai, Mohammad-Reza; Norouzi, Behzad (Zootaxa, 2020)
Seven genera and more than 98 species of mosquitoes (Diptera: Culicidae) are found in southwestern Asia (Harbach 1988). The most recent checklist of Iranian mosquitoes includes 69 species representing either seven or 11 genera depending on the classification used for aedines (Azari-Hamidian et al. 2019). Orthopodomyia pulcripalpis (Rondani) was the most recent genus and species to be added to the Iranian mosquito fauna (Azari-Hamidian et al. 2017).